Prevalence and comorbid for late-stage chronic kidney disease (CKD) in patients undergoing continuous ambulatory peritoneal dialysis (CAPD) due to urinary obstruction - Hafidz Hanafi; Besut Daryanto; Atma Gunawan (Universitas Nahdlatul Ulama Surabaya, 2024)
Chronic Kidney Disease (CKD) is a condition of gradual or chronic decline in kidney function, which is quite severe and caused by various kidney diseases, including urinary obstruction. This disease is progressive and generally irreversible. CKD requires kidney replacement therapy, one of which is continuous ambulatory peritoneal dialysis (CAPD). To determine the prevalence and risk factors for End Stage Renal Disease (ESRD) in patients undergoing CAPD due to urinary obstruction. We performed a retrospective cohort with a cross-sectional study was conducted using secondary data from medical record data of ESRD patients with CAPD accompanied by urinary obstruction at Dr. Saiful Anwar General Hospital, Malang, Indonesia. The prevalence of CKD in patients with CAPD accompanied by urinary obstruction was 6,50% and dominated by males (57,8%) with an age range of 41-50 years (26%). The majority of comorbidities are severely high the Body Mass Index (BMI) (89,0%) and hypertension (80,8%). The location of obstruction is mostly unilateral (5,64%) with mild levels (4,06%). Urinary obstruction is a frequent clinical finding in CKD patients with CAPD. The most common risk factor in this study was hypertension. The prevalence and comorbidities among CAPD patients with Urinary obstruction (UO) are better understood because to this study. It is necessary to recognise its limitations, particularly the small sample size and single-centre design. Future studies should involve more centres and larger patient groups in order to provide a more thorough knowledge of the mechanisms behind the high survival rates among CAPD patients.